Made in Wood : Work from the Western Cape. - South African National Gallery, Cape Town (Cape Town : South African National Gallery, 1992)
Appollis, Tyrone ; Bailey, Beezy ; Bester, Willie ; Brand, Kevin ; Brown, David ; Davis, Bill ; Disner, Solly ; Goldberg, Michael ; Kottler, Moses ; Lipshitz, Lippy ; Makeleni, Isaac ; Margalit, Nathan ; etc.
Made in Wood : Work from the Western Cape, South African National Gallery, Cape Town, 12.12.1992 - 28.2.1993
boek